Using Array‐Derived Rotational Motion to Obtain Local Wave Propagation Properties From Earthquakes Induced by the 2018 Geothermal Stimulation in Finland - G. Taylor; G. Hillers; T. A. T. Vuorinen (Geophysical Research Letters)
Abstract We estimate vertical rotation rates for 204 earthquakes that were induced by the 2018 stimulation of the Espoo/Helsinki geothermal reservoir from wavefield gradients across geophone arrays. The array‐derived rotation rates from seismograms recorded at 6–9 km hypocentral distances vary between 10−9 and 10−7 rad s−1, indicating a comparable sensitivity to portable rotational instruments. Using co‐located observations of translational and rotational motion, we estimate the local propagation direction and the apparent phase speed of SH waves, and compare these estimates with those obtained by S wave beamforming. Propagation directions generally align with the earthquake back azimuths, but both techniques show deviations indicative of heterogeneous seismic structure. The rotational method facilitates a station‐by‐station approach that resolves site specific variations that are controlled by the local geology. We measure apparent S wave speeds larger than 5 km s−1, consistent with steep incidence angles and high propagation velocities in the Fennoscandian Shield.